ISOLATION AND MOLECULAR CHARACTERIZATION OF PASTEURELLA MULTOCIDA FROM COMMERCIAL LAYER FLOCKS SUFFERING FROM RESPIRATORY SYNDROMES - M. D. Mehmood; M. H. Qazi; K. Muhammad2; M. Shahid; M. Akram; F. Amin; M. Gul; M. A. Ali (Journal of Animal and Plant Sciences, 2016)
A total of five sick birds showing respiratory syndromes from each of the five commercial layer flocks of Karachi, Lahore, Vehari and Toba Tek Singh were selected and slaughtered. Liver, heart and long bones from each of the birds were collected and inoculated on brain heart infusion blood agar (BHI-BA). Inoculated agar plates were incubated at 37oC for 24 hours. Small pin head sized non hemolytic colonies having bipolar gram negative coccobacilli were observed. The isolates did not grow on MacConkey’s agar and showed positive reaction to indole and H2S production. The DNA of each bacterial isolate was amplified using universal and capsular serotype specific primers of P. multocida. The isolates showing amplicons of 590 and 1048bps, respectively were declared as P. multocida type A. These isolates were recovered 100, 60, zero and 20% from Karachi, Lahore, Vehari and Toba Tek Singh, respectively. It was concluded that clinical signs, post mortem changes, cultural and microscopic characteristics, biochemical profile and molecular characterization confirmed the causative agent of the disease as P. multocida serotype A.
Keywords: Fowl cholera; Layer farms; Polymerase chain reaction; Brain heart infusion blood agar; Pasteurella multocida